2020
DOI: 10.1038/s41419-020-02979-9
|View full text |Cite
|
Sign up to set email alerts
|

DRAM1 plays a tumor suppressor role in NSCLC cells by promoting lysosomal degradation of EGFR

Abstract: Lung cancer is the leading cause of cancer-associated mortality worldwide. DNA damage-regulated autophagy modulator 1 (DRAM1) plays an important roles in autophagy and tumor progression. However, the mechanisms by which DRAM1 inhibits tumor growth are not fully understood. Here, we report that DRAM1 was decreased in nonsmall-cell lung carcinoma (NSCLC) and was associated with poor prognosis. We confirmed that DRAM1 inhibited the growth, migration, and invasion of NSCLC cells in vitro. Furthermore, overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 52 publications
(59 reference statements)
2
11
0
Order By: Relevance
“… 42 Its acts as a tumor inhibitor in non-small-cell lung carcinoma (NSCLC) by promoting epidermal growth factor receptor (EGFR) lysosome degradation and regulates autophagy as well as cell proliferation by inhibiting the phosphatidylinositol 3-kinase-Akt-mechanistic target of rapamycin (mTOR)-ribosomal protein S6 pathway. 43 , 44 It has been reported that DNER promotes the epithelial-to-mesenchymal transition in breast cancer through the Wnt/β-catenin pathway. 45 DAPL1 was upregulated in hepatoblastoma and could be used as a prognostic biomarker of the disease.…”
Section: Discussionmentioning
confidence: 99%
“… 42 Its acts as a tumor inhibitor in non-small-cell lung carcinoma (NSCLC) by promoting epidermal growth factor receptor (EGFR) lysosome degradation and regulates autophagy as well as cell proliferation by inhibiting the phosphatidylinositol 3-kinase-Akt-mechanistic target of rapamycin (mTOR)-ribosomal protein S6 pathway. 43 , 44 It has been reported that DNER promotes the epithelial-to-mesenchymal transition in breast cancer through the Wnt/β-catenin pathway. 45 DAPL1 was upregulated in hepatoblastoma and could be used as a prognostic biomarker of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the overexpression of miR-524-5p is associated with a poor prognosis of patients with idiopathic pulmonary fibrosis [ 28 ]. Considering the previously reported findings [ 24 , 28 , 31 ], we examined the role of miR-524-5p in HCC827 and NCI-H1650 cell lines and found that the enrichment of miR-524-5p was significantly lower than EGFR-AS1, and that they were inversely expressed in HCC827 and NCI-H1650 cell lines. Subsequently, the inhibition of miR-524-5p promoted the viability and invasion of HCC827 and NCI-H1650 cell lines.…”
Section: Discussionmentioning
confidence: 94%
“…Emerging evidence suggested that DRAM1 is engaged in the biological functions of cancer cells [ 30 , 43 ]. DRAM1 has been found to play a tumor suppressor role in NSCLC [ 31 ]. However, DRAM1 expression and clinical significance in lung cancer have not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of DRAM1 has been shown to increase basal levels of autophagosome numbers, indicating that DRAM1 can act early in the autophagy process, contributing to autophagosome formation (Mah et al, 2012). However, the DRAM1 protein predominantly localizes to lysosomes and there is evidence also for functions at later steps in the process, showing that DRAM1 enhances autophagic flux and promotes ATPase activity and lysosomal acidification (Zhang et al ., 2013; Geng et al ., 2020). DRAM1 is thought to mediate crosstalk between autophagy and apoptosis by interacting with the proapoptotic protein BAX (Guan et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%